STUDY ON EMISSIONS OF CARBON DIOXIDE FROM GRAZED PASTURE LAND USING CATTLE URINE - B. Thulasamma; Ch. Harikrishna; A. Saratchandra; P. Amareswari; D.B.V. Ramana (Indian Journal of Veterinary and Animal Sciences Research, 2025)
An experiment was conducted to assess the effect of application of cattle urine at a rate of 0.7 l/m2 area on carbon dioxide (CO) emissions under low, medium and high pasture cover blocks of the grazing area during rainy season at Hyderabad. CO2 emissions was significantly (P<0.05) higher in experimental plots which received cattle urine than without cattle urine. Mean CO2 concentration increased linearly with the time i.e., from 0 to 60 minutes of sample collection under different pasture cover blocks and the differences were significantly (P<0.01) different. The CO2 emissions flux (mg/m /h) ranged from 9.10 to 28.80, 12.30 to 27.80 and 10.40 to 32.50 with a mean of 16.50 ± 1.24, 17.50 ± 1.00 and 21.30 ± 1.58 mg/m2/h under low, medium and high vegetation covered chambers, respectively and no trend was observed in CO2 flux among different vegetative cover blocks. The differences in mean CO2 emissions flux among different vegetation cover plots were significantly (P<0.05) different with highest under high vegetation and lowest under low vegetation cover. It is concluded that, pasture growth would influence the CO2 emissions from the grazing lands when applied urine of grazing animals hence, appropriate pasture management combined with rotational livestock grazing helps in containing global warming.